Mechanical alloying of Sm and Fe mixtures having the molar ratio of 1/2 and 1/3 - S. Thongmee (2018)
The mechanical alloying of Sm-Fe mixtures of molar ratios 1/2 and 1/3 were carried out. The milled mixtures were subjected to a two-step annealing process; first annealing for 1 h at 900 °C in argon gas, followed by a second annealing for 4 h at temperatures between 300 and 450 °C (Ta2) in nitrogen gas. Both the X-ray diffraction (XRD) and Moessbauer studies indicate that heat treatment of both mixtures results in the growth of the 2-17 (Sm2Fe17Nx) intermetallic. The coercivity of both milled mixtures increases as Ta2is raised, while the specific magnetization of both are seen to decrease initially and then increase as Ta2is raised further.